Epidemiology of Canine Gastrointestinal Parasites in Central Plain Zone of Punjab - sachan, supriya; Singh Bal, Mandeep; Mahajan, Vishal; Kaur, Paramjit; Das Singla, Lachhman (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The aim of this study was to explore, the epidemiology of gastro-intestinal parasites and its associated risk factors affecting canine  population of the central plain zone of Punjab, India. The faecal samples were collected form 525 dogs and were subjected to conventional  parasitological techniques to identify parasitic oocysts and/or eggs. The overall occurrence of 60.2% was observed which comprised of  53.3% of individual parasitic infection and 6.9% of mixed parasitic infections. The hookworms (31.24%) were found to be predominant  enteric parasite followed by Toxocara (11.43%), Dipylidium (3.81%), Coccidia (3.43%), Taeniids (2.29%) and Trichuris (1.14%), whereas  mixed infection of gastrointestinal parasites was 6.86%. The associated risk factor analysis for the occurrence of enteric parasites revealed  significantly higher infection in non-descript (70.67% vs 56.47%), stray (64.38% vs 54.94%), non-dewormed (74.26% vs 48.61%) and  urban (63.86% vs 54.41%) dwelling dogs compared to well defined, pet, dewormed and rural dogs, while a non-significant association  was observed in young (62.7% vs 56.54%), female (62.75% vs 57.91%) and non-vaccinated dogs (63.14% vs 41.46%) compared to older,  male and vaccinated dogs, with higher seasonal prevalence in winter than summer and monsoon (63% vs 57.41%). The current study is  an attempt towards a systematic epidemiological report from different districts which would be helpful in the control and mitigation  of the gastrointestinal parasitism in dogs, which might act as a potential public health concern.
Keywords: Central plain zone; Dogs; Epidemiology; Gastrointestinal parasitism; Public health